The English lyric from Wyatt to Donne : a history of the plain and eloquent styles - Peterson, Douglas L. (Princeton legacy library., 2015)
The author rejects C.S. Lewis's theory of a "Drab" and a "Golden" school as unhistorical, and establishes the presence of an eloquent or courtly tradition and of a plain or contemplative tradition. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905